Attitudes of Islamic Learning and Education Faculty Students towards English Language at Karachi University - Iqbal, Nayab; Aftab, Huma; Azhar, Kaukab Abid (JET (Journal of English Teaching), 2019)
The research paper aims at studying the attitudes of the students of Islamic Learning and Education Faculty towards English at the University of Karachi. It is based on testing the hypothesis that the students of Islamic Learning Faculty have less positive attitudes towards English as compared to the students of Education faculty through a survey on first year students of both faculties. A five-point Likert scale was used to conduct a survey on 151 students of the Islamic Learning faculty and 135 students of the Education faculty. The results were calculated using an independent t-testand standard deviation which reveals that there is a minor difference in the attitudes of thestudent of both faculties. The students of the Education faculty showed more positive attitudes when asked about the importance of English as compared to the attitudes of the students of Islamic Learning Faculty. However, the difference in their attitude is negligible. As the results reveal a minor association between the attitudes of the learners and their faculty, the study; therefore, proves the null hypothesiswhich says that there is no significant difference between the attitudes of the students of both the faculties. Keywords: attitudes; English language; t-test; standard deviation; Islamic learning faculty; education faculty; likert-scales